DAMPAK DISIPLIN KERJA TERHADAP KINERJA GURU PADA SMA NEGERI 1 KERITANG KECAMATAN KERITANG KABUPATEN INDRAGIRI HILIR - Fakhri, Rizqi (Eko dan Bisnis: Riau Economic and Business Review, 2021)
Abstract : The study wasconducted in SMA Negeri 1 Keritang Kecamatan Keritang Kabupaten Indragiri Hilir. Based on the background of the research stated above, the writer can formulate the problem of teachers at SMA Negeri 1 Keritang. The purpose of this study was to see the effect of work on teacher performance in SMA Negeri 1 Keritang. Data analysis carried out in this study was carried out using descriptive and quantitative methods with a total of 47 respondents, based on the above ouput obtained t_count of 16,999 while t_table obtained 2,0141 so this can judge that the value of t_count (16,999)> of t_table(2,0141), so that could concluded that there isa significant effect between discipline on the performance teacher or reject H0 and then could obtained value R_square or coefficient determination equal to 0,65 which has meaning magnitude influence variable free/discipline to variable bound/performance as big as 86,5% whereas the rest as big as 13,5% describes variable free others who don’t observed in research this.